A Universal Language Translator: Is This the Future or the Doom of Language Learning? - Andre Syafrony; Vica Ananta Kusuma (LPPM Universitas Terbuka, 2022)
Artificial Intelligence-based universal language translation system allows users in the Metaverse to better communicate with each other. Meta points to construct an all-inclusive dialect interpretation framework to permit clients to relate to others within the Metaverse without stressing almost dialect obstructions. Zuckerberg uncovered that Meta is working on building an AI-powered